Analisis Tentang Pengaruh Pelatihan dan Keterampilan Terhadap Keberhasilan Usaha Mitra Binaan PT Karya Masyarakat Mandiri Dompet Dhuafa Republika - Kosasih Kosasih (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2019)
The purpose of this research was to obtain empirical evidence through data analysis on the influence of training and skills on the businesses success of PT Karya Masyarakat Mandiri Dompet Dhuafa Republika fostered partner in the Jakarta Region. The research method used in this research is descriptive and verification method with a quantitative approach and uses multiple linear regression analysis. Data collection techniques used were observation on 6 fostered partners in the Jakarta Region, 50 respondents through questionnaires equipped with interviews. The results showed that both partially and simultaneously between training and skills had a positive effect on business success. This means that the better the training and skills of the fostered partners, will be successful the business. As well as the most dominant influenced to business success is skill, meaning that with good skills, business success automatically increases.